2003
DOI: 10.1073/pnas.0307228101
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of mammalian protein O -mannosyltransferase activity: Coexpression of POMT1 and POMT2 required for enzymatic activity

Abstract: Defects in O-mannosylation of ␣-dystroglycan are thought to cause certain types of congenital muscular dystrophies with neuronal migration disorders. Among these muscular dystrophies, WalkerWarburg syndrome is caused by mutations in the gene encoding putative protein O-mannosyltransferase 1 (POMT1), which is homologous to yeast protein O-mannosyltransferases. However, there is no evidence that POMT1 has enzymatic activity. In this study, we first developed a method to detect protein O-mannosyltransferase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
279
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 344 publications
(287 citation statements)
references
References 44 publications
5
279
0
3
Order By: Relevance
“…Second, GnT-III may associate with some other molecules, which define the specificities for protein or peptide substrates. Several studies have shown that the glycosyltransferase complex formation may play a crucial role in the determination of both activity and substrate specificity [35,36]. Third, each glycosyltransferase may have its own pathway to operate glycosylation in Golgi apparatus.…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%
“…Second, GnT-III may associate with some other molecules, which define the specificities for protein or peptide substrates. Several studies have shown that the glycosyltransferase complex formation may play a crucial role in the determination of both activity and substrate specificity [35,36]. Third, each glycosyltransferase may have its own pathway to operate glycosylation in Golgi apparatus.…”
Section: Roles Of N-glycosylation On α5β1 Integrinmentioning
confidence: 99%
“…11, 42 The idea that mutations in both of these genes cause disease is consistent with the demonstration by Endo and colleagues that in flies RNA INTERFERENCE knockdown of POMT1 and POMT2 yields the same phenotype (rotated abdomen), 43 and that coexpression of POMT1 and POMT2 is required for Omannosyltransferase activity in mammalian cell lines. 44 Pomt1 has also been eliminated in mice. 45 The phenotype of these animals-embryonic lethality due to disruption of REICHERT'S MEMBRANE-is the same phenotype that is found in mice lacking Dag1.…”
Section: Dystroglycanopathy-gene Function: Some Mysteries Remainmentioning
confidence: 99%
“…3 Protein O-mannosyltransferase 2 (POMT2) is a 21-exon gene that encodes an integral membrane protein of the endoplasmic reticulum required for the correct glycosylation of a-dystroglycan. 4,5 Both POMT1 and POMT2 mutations are the most common causes of WWS. 1, 2,6,7 Cardiac involvement among the dystroglycanopathies remains poorly characterized.…”
Section: Introductionmentioning
confidence: 99%